2018
DOI: 10.3390/molecules23040761
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking Studies, In Vitro Antimicrobial and Antifungal Activities of Novel Dipeptide Derivatives Based on N-(2-(2-Hydrazinyl-2-oxoethylamino)-2-oxoethyl)-Nicotinamide

Abstract: A series of linear dipeptide derivatives (4–10) were prepared and evaluated as antimicrobial agents via the synthesis of N-(2-(2-hydrazinyl-2-oxoethylamino)-2-oxoethyl) nicotinamide (4). Compound 4 was reacted with 4-chlorobenzaldehyde or 4-hydroxybenzaldehyde, to give the hydrazones 5 and 6, respectively. On the other hand, Compound 4 was coupled with phenylisocyanate or methylisothiocyanate to give Compounds 7 and 8, respectively. The latter compounds (7 and 8) were coupled with chloroacetic acid to give oxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In our previous studies of amino acid and peptide derivatives, gave a good antimicrobial properties, anti-inflammatory, analgesic agents 44–48 and anticancer activities 26–28 , 49 , as well as, pyrazoloderivatives as anticancer agents 50 . Thus, our study aims to conjugate l -alanine and isophthalic acid.…”
Section: Resultsmentioning
confidence: 98%
“…In our previous studies of amino acid and peptide derivatives, gave a good antimicrobial properties, anti-inflammatory, analgesic agents 44–48 and anticancer activities 26–28 , 49 , as well as, pyrazoloderivatives as anticancer agents 50 . Thus, our study aims to conjugate l -alanine and isophthalic acid.…”
Section: Resultsmentioning
confidence: 98%
“…In all biological kingdoms, CYP51 orthologs are located and united into one (CYP51) family (despite very low identity sequence of amino acid across phylogeny) [ 23 ]. Depending on these observations and in continuation of our previous studies for anti-microbial and anticancer agents [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], this study was aimed at synthesizing a series of novel dipeptide compounds that were hypothesized to affect systemic anti-microbial measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, peptides comprise a major group of pharmaceutical drugs with potential anticancer effects [7]. Previous reports showed that chemical synthesis of peptides proved successful in obtaining new derivatives with potent antimicrobial, anti-inflammatory [8][9][10][11][12][13][14][15][16], and anticancer properties [17][18][19][20][21]. In our previous works, we were able to synthesize, chemically characterize, and biologically evaluate different bis-amino acid and peptide conjugates of dipicolinic acid [22].…”
Section: Introductionmentioning
confidence: 99%